2007
DOI: 10.1152/ajpcell.00496.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 responses to aging and unloading-induced skeletal muscle atrophy

Abstract: Pistilli EE, Siu PM, Alway SE. Interleukin-15 responses to aging and unloading-induced skeletal muscle atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 45 publications
4
54
1
Order By: Relevance
“…Our laboratory has previously suggested that skeletal muscle increases IL-15 mRNA concentrations in response to atrophic stimuli, as a molecular attempt to counter muscle loss [3]. In this study, we tested the hypothesis that IL-15 would attenuate apoptosis within aged skeletal muscles by increasing circulating levels of IL-15 protein in aged rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our laboratory has previously suggested that skeletal muscle increases IL-15 mRNA concentrations in response to atrophic stimuli, as a molecular attempt to counter muscle loss [3]. In this study, we tested the hypothesis that IL-15 would attenuate apoptosis within aged skeletal muscles by increasing circulating levels of IL-15 protein in aged rats.…”
Section: Discussionmentioning
confidence: 97%
“…Skeletal muscle expresses mRNAs for both IL-15 [2] and the three components of the IL-15 receptor (IL-15R: IL-15Rα, IL-2R/IL-15Rβ, γc) [3]. While conditions that promote muscle atrophy (i.e.-aging, disuse) have been shown to alter IL-15 mRNA concentrations within skeletal muscle [3], the role that the IL-15/IL-15R axis plays in skeletal muscle remains not fully elucidated. Production of mature IL-15 protein is tightly regulated at the levels of protein translation and vesicle trafficking, explaining in part, why mature IL-15 protein has been difficult to measure in biological fluids [4].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated from gastrocnemius muscles, spleen, and kidney of IL-15Rα-KO mice and B6129 control mice as previously described (4). RNA quantity and integrity were assessed using a Nano-Drop 2000 Spectrophotometer (Thermo Scientific); the 260/280 ratio for all samples used was between 1.9 and 2.1.…”
Section: Taqman Qpcrmentioning
confidence: 99%
“…The plasma membrane receptor for IL-15 was initially characterized as trimeric in structure, composed of IL-2 receptor β (IL-2Rβ), the common gamma chain (γc), and a specific IL-15Rα chain (2,3). Transcripts for IL-15 and IL-15Rα have a wide tissue distribution, and skeletal muscle tissue contains an abundance of IL15 and IL15RA mRNAs (1,2) that are responsive to atrophic stimuli (4), muscle contraction (5), and aging (4,6,7). In vitro experiments in myogenic cells initially suggested that IL-15 was an anabolic factor for skeletal muscle, able to stimulate the accumulation of contractile protein in differentiated myotubes (8)(9)(10).…”
mentioning
confidence: 99%
“…43 RNA quantity and integrity was accessed using a NanoDrop spectrophotometer (Thermo Scientific, Wilmington, DE); the 260/280 ratio for all samples used was between 1.9 and 2.1. Two micrograms of total RNA was reverse transcribed to make cDNA using a high-capacity cDNA reverse transcription kit according to the manufacturer's instructions (Applied Biosystems, Foster City, CA).…”
Section: Qpcr Gene Expression Analysismentioning
confidence: 99%